The Effect of Human Adipose-Derived Mesenchymal Stem Cell (HADMSC) With Chitosan Scaffold on Bone Defect White Rats (Rattus Norvegicus) on Serum Alkaline Phosphatase (ALP) Levels - Fauzan Fauzan (Journal of Stem Cell Research and Tissue Engineering, 2022)
Bone defect is one of the challenges for dentists in the process of healing bone tissue. Bone defect can occur in alveolar bone with the etiology of microorganisms and cyst expansion. In addition, cases of bone defects in alveolar bone are also often found in cases with treatment of apex resection and hemisection. Autologous bone graft is a clinical gold standard in the treatment of bone defect. However, the use of bone graft has a limited number of growth factors produced. Tissue engineering is the latest method in terms of bone regeneration. Tissue engineering has three main components; stem cell, growth factor, and scaffold. Stem cells will increase osteoblastogenesis and chitosan scaffold will immobilize alkaline phosphatase (ALP) so that serum ALP levels decrease and bone regeneration and mineralization processes become faster. The aim of this study is analyzing the effect of human adipose-derived mesenchymal stem cell (HADMSC) with chitosan scaffold (CS) in bone defect on serum alkaline phosphatase (ALP) levels. This research was a in vivo laboratory experimental study. Bone defects are planted with chitosan scaffold (CS) and a combination of human adipose-derived mesenchymal stem cells (HADMSC) with chitosan scaffold. Measurement of ALP levels was carried out by the International Federation of Clinical Chemistry (IFCC) method using an analyzer on the 1st, 3rd, 7th and 14th days. Research data were analyzed using multivariate analysis of variance (MANOVA) and Bonferroni tests. The results of the data analysis showed that there were significant differences in ALP levels with CS planting and the combination of HADMSC and CS. the effect of human adipose- derived mesenchymal stem cell (HADMSC) with chitosan scaffold (CS) on bone defect reduces serum alkaline phosphatase (ALP) levels on the 3th and 14th days.